Percepções de estudantes acerca da relação das atividades de robótica com os pilares do pensamento computacional : estudo de caso em um espaço maker de uma escola privada de Porto Alegre - Rocha, Gabriel Gomes (2023)
Among the challenges offered by the context of cyberculture established by the digital world, the biggest one is to prepare students to deal with a world of constant change and uncertainty about what work activities will be like. How to organize teaching and learning processes challenges teachers and school administrators. One strategy to overcome these challenges is considering the habits and competencies associated with constructing computational solutions in the school environment. In this sense, the BNCC integrates Computational Thinking (CP) into the set of skills and competencies to be developed by the students. The challenge for teachers and students is understanding what CT means and how to crosscut this way to build solutions in other areas of knowledge. This qualitative research, based on a case study, had the general objective of understanding, from the perceptions of students at a private school, of primary education, in the city of Porto Alegre (RS), the relationship between Robotics activities carried out in maker space, with the pillars of the PC. Data collection took place from a booklet, in which the students recorded, at each meeting, the learning they built together with their colleagues and the teacher at that time. The collected data uses the Discursive Textual Analysis method, with a priori categories: Decomposition; Pattern Recognition; Abstraction; and Algorithms. In the analysis, it was possible to verify how the relationship between Robotics and the pillars of Computational Thinking took place from the students' perceptions. The main result was that problem-solving took place more thoughtfully and assertively. The debugging and correcting intercurrences allowed students to understand the importance of errors in the process and learning. It is an opportunity to review pedagogical practices and integrate new ways of thinking about problem-solving in all curricular subjects